Effect of long term cold storage and microwave extraction time on the physical and chemical properties of citrus pectin. (July 2019) - Fishman, Marshall L.; Chau, Hoa K.; Hotchkiss, Arland T.; White, Andre; Garcia, Rafael A.; Cooke, Peter H.
Abstract: Pectin, acid-extracted by microwave heating under pressure from orange and lime albedo, was cold (−20 °C) stored for 14 years and the physical and chemical properties were compared to the properties of the original microwave-extracted pectin prior to cold storage. The pectin physical and chemical properties were measured by using multi-detector high performance size exclusion chromatography (HPSEC), atomic force microscopy (AFM), amino acid, monosaccharide and degree of esterification compositional analysis following cold storage. The weight average molar mass (Mw ), intrinsic viscosity (ηw ) and radius of gyration (Rgz ) changed following cold storage depending on the time of microwave extraction, but all three parameters decreased with extraction time for both orange and lime pectin, regardless of whether they were analyzed before or after cold storage. All pectin samples had little or no appreciable difference in galacturonic acid content following cold storage, yet the degree of esterification decreased by approximately 50% and total sugar content increased following cold storage for both orange and lime pectin. Homogalacturonan (HG) was the major cold-stored pectin component with lower amounts of rhamnogalacturonan I (RG I) containing arabinogalactan side chains present in pectins extracted for shorter times. Amino acid analysis indicated that protein associated with pectin was enriched in aspartic acid/asparagine, glutamic acid/asparagine, leucine and lysine with UV absorbing phenylalanine and tyrosine also present in cold-stored pectin. UV detection in HPSEC chromatograms for both orange and lime pectins following cold storage, revealed that more protein was associated with higher molar mass pectin at 2.5 min of extraction time. By 10 min of extraction time, there was a larger breakdown of high molar mass pectin and protein shifted to a lower molar mass distribution weight fraction. AFM images showed that small spherical molecules, segmented rods and kinked rods were present in both orange and lime pectin following cold storage. Graphical abstract: Effect of long term cold storage and microwave extraction on pectin.Image 1 Highlights: Pectin degree of esterification decreased by 50% following cold storage. Pectin total carbohydrate content increased following cold storage. Yet pectin galacturonic acid content remained unchanged following cold storage. Segmented rod and spherical structures were observed by AFM following cold storage. Pectin-associated protein was degraded to lower molar mass during extraction.